ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA LEMBAGA PENDIDIKAN DI KECAMATAN DAMPIT - Kinanthi Widya Larasati; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe purpose of this study was to determine the effect of management support, training and education programs, user technical capabilities, and user involvement on the performance of accounting information systems in educational institutions in Dampit District. The target population used in this study is an information system user (operator) located in Dampit District education institution. Because the sample must meet several conditions set by the researcher, this study uses a purposive sampling technique. Data is collected by distributing questionnaires to respondents who have met the specified conditions. Data processing of the answers from the questionnaires that have been collected is fully carried out using SPSS 16.0. Keywords: Management Support, Training and Education Programs, User Technical Capabilities, User Engagement, Accounting Information System Performance.